Analisis Kebutuhan E-Assessment Four Tier Multiple Choice pada Materi Getaran Harmonis Berbasis Literasi Sains - Nur Afni Fuji Alivia; Fatni Mufit (Lembaga Yasin AlSys, 2026)
Students’ low scientific literacy, particularly in physics topics such as harmonic vibrations, remains a major problem in learning. This condition is partly caused by the use of assessment instruments that are not yet able to measure conceptual understanding in depth and identify students’ misconceptions. This study aimed to analyze the need for developing a four-tier multiple-choice e-assessment as an instrument for assessing students’ scientific literacy. This study used a descriptive qualitative approach with a needs analysis design. The research participants consisted of eleventh-grade students and physics teachers selected through purposive sampling. Data were collected through questionnaires, semi-structured interviews, and documentation studies, and then analyzed using descriptive qualitative techniques with an interactive model. The results showed that the assessment instruments currently used were still oriented toward lower-order cognitive abilities and had not comprehensively integrated scientific literacy indicators. In addition, students had difficulty understanding physics concepts contextually, while teachers needed assessment instruments that were more diagnostic and technology-based. The conclusion of this study emphasizes a high need for developing a four-tier multiple-choice e-assessment that is able to identify misconceptions and measure students’ scientific literacy more accurately. The implications of this study indicate that the development of this instrument can serve as an innovative solution for improving the quality of physics assessment and learning, while also providing a basis for developing technology-based evaluation that is more effective and aligned with the demands of 21st-century learning.